Extended-spectrum β-lactamase and carbapenemase producing Enterobacteriaceae among patients suspected with surgical site infection at Hospitals in Southern Ethiopia - Odoko, Desta; Kumalo, Abera; Alemu, Getachew; Demisse, Tigistu; Mulugeta, Teshale; Temesgen, Muluneh (Frontiers in Microbiology, 2024)
Background:-Extended-spectrum β-lactamase and Carbapenemase-producing Enterobacteriaceae are an increasing problem for patients today. Data on clinical samples for ESBL and Carbapenemase-producing Enterobacteriaceae for surgical site infection patients in developing countries are limited, including Ethiopia, mainly due to resource constraints. Hence, this study aimed to determine the prevalence of extended-spectrum beta-lactamase-and Carbapenemaseproducing Enterobacteriaceae among patients suspected to have surgical site infection at Hospital in Southern Ethiopia.A hospital-based cross-sectional study was conducted on 422 suspected surgical site infections from June 1, 2022 to August 30, 2022 at Hospitals in Southern Ethiopia.Sociodemographic and clinical data were obtained by using a structured questionnaire. Clinical samples (pus, pus aspirates, and wound swabs) were collected aseptically and processed within 30 minutes by placing the swabs in sterile test tubes containing sterile normal saline (0.5 mL).Samples were cultured on blood and MacConkey agar plates. All positive cultures were characterized by colony morphology, Gram staining, and standard biochemical tests. Antimicrobial sensitivity tests were performed using Kirby Baur disk diffusion on Mueller-Hinton agar. ESBL production was confirmed using a double-disc synergy test (DDST) method. Carbapenemase production was assessed using the modified Hodge test. Logistic regression analysis was used to determine associated factors. A P-value less than 0.05 were considered statistically significant.Result: Bacteria belonging to the order Enterobacterales were cultured in 23.7% out of 422 patients with suspected surgical wound infection. Of all the isolates, Enterobacteriaceae (69 isolates) were the most frequent, with E. coli (29/69) followed by K. pneumoniae (14/69). Of 69 Enterobacteriaceae isolates, 66.6 % (46/69) were positive for ESBL production, and 21.7 (15/69) were positive for carbapenemase-producing Enterobacteriaceae. The majority of Enterobacteriaceae isolates showed sensitivity to meropenem (72.1%); however revealed 63.9% and 70.5% were resistant to gentamicin and ciprofloxacin, respectively. Similarly, a higher resistance rate to cefepime (91.8%), amoxicillin-clavulanic acid (98.4%), ceftriaxone (95.1%), and ceftazidime (91.8%). .Study results showed the severity of ESBL-producing Enterobacteriaceae is critical and CPE is alarming. Meropenem is the most effective antibiotic against the ESBL-producing Enterobacteriaceae.